Effects of feeding on different parts of Ailanthus altissima on the intestinal microbiota of Eucryptorrhynchus scrobiculatus and Eucryptorrhynchus brandti (Coleoptera: Curculionidae) - Ma, Tian-Chi; Guo, Wen-Juan; Wen, Jun-Bao (Frontiers in Microbiology, 2022)
Eucryptorrhynchus brandti and E. scrobiculatus (Coleoptera: Curculionidae) are two monophagous weevil pests that feed on Ailanthus altissima (Mill.) Swingle but differ in their diet niche. In the field, adults of E. brandti prefer to feed on the trunk of A. altissima, whereas adults of E. scrobiculatus prefer to feed on the tender parts. We conducted Illumina sequencing of 16S rRNA to examine changes in bacterial diversity in the adults of these two weevil species after they fed on different parts of A. altissima (trunk, 2- to 3-year-old branches, annual branches, and petioles). Proteobacteria, Tenericutes, and Firmicutes were the dominant phyla in E. brandti (relative abundance was 50.64%, 41.56%, and 5.63%, respectively) and E. scrobiculatus (relative abundance was 78.63%, 11.91%, and 7.41%, respectively). At the genus level, Spiroplasma, endosymbionts2, uncultured_bacterium_f_Enterobacteriaceae, and Lactococcus were dominant in E. brandti, and uncultured_bacterium_f_Enterobacteriaceae, Wolbachia and Spiroplasma, and endosymbionts2 were dominant in E. scrobiculatus. Linear discriminant analysis effect size analysis revealed that uncultured_bacterium_f_Enterobacteriaceae in the adults of both weevil species was derived from the petioles. Adults of E. brandti may require the trunk, and adults of E. scrobiculatus may require the petioles and annual branches to maintain the high diversity of their gut microbes. Phylogenetic analysis of three operational taxonomic units (OTUs) of endosymbionts2 (Nardonella) was performed to clarify the relationships between the two weevil species and endosymbionts2. Although no divergence between the two weevil species was discovered, the three OTUs of endosymbionts2 in this study may represent a new Nardonella species. The results of this study indicate that feeding on different parts of A. altissima affects the composition and function of the microbes of E. brandti and the microbial composition of E. scrobiculatus. Variation in the abundance of Wolbachia and Spiroplasma in E. brandti and E. scrobiculatus is associated with dietary niche changes, and this might explain the evolution of reproductive isolation between these two sibling weevil species.